The Qurʾanic School in Iraq: Origins, Development, and Contemporary Trends - Ali, Zahra (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
This study examines the Qurʾanic school in Iraq as one of the most influential intellectual traditions in the history of Qurʾanic studies, tracing its origins, development, and contemporary trends. From the early Islamic period, major Iraqi cities such as Kufa, Basra, and Baghdad played a central role in shaping distinctive approaches to Qurʾanic interpretation and related sciences. The study highlights the methodological features of the Iraqi Qurʾanic school, beginning with reliance on transmitted interpretation (tafsīr bi al-maʾthūr), followed by the integration of linguistic, grammatical, juristic, and rational approaches to understanding the Qurʾanic text. It further explores the evolution of this school in later periods, leading to modern trends characterized by methodological renewal, including thematic interpretation, maqāṣid-based studies, and engagement with contemporary linguistic and human sciences. The study concludes that the Qurʾanic school in Iraq represents a dynamic scholarly model that balances adherence to classical tradition with openness to intellectual renewal and contemporary challenges.